2014
DOI: 10.1007/s10554-014-0480-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hemodialysis, left ventricular mass and FGF-23 on myocardial mechanics in end-stage renal disease: a three-dimensional speckle tracking study

Abstract: Left ventricular (LV) hypertrophy and one of its inducers, the fibroblast growth factor-23 (FGF-23) were found to be associated with unfavourable outcome in end-stage renal disease (ESRD) patients. We sought to investigate the influence of hemodialysis (HD), increased LV mass and FGF-23 on LV mechanics using three-dimensional (3D) speckle tracking echocardiography. Forty-four ESRD patients on maintenance HD were examined just before and immediately after HD, and were compared to 44 normal controls (NC). Transt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…They concluded from results that serum FGF23 level is independently associated with LVH; however, it is not a predictor for short-term prognosis (2-year follow-up). [22] In a recent study, Kovács and colleagues [23] by using three-dimensional speckle tracking echocardiography investigated the effects of FGF23 on LV mechanics in patients on hemodialysis and found that elevated FGF23 levels were associated with increased LV mass (ρ = 0.581, P < 0.001). Accordingly, Liu et al [24] examined the relationship between FGF23and LVH in 62 patients on continuous ambulatory peritoneal dialysis and 30 healthy controls [24] .…”
Section: Discussionmentioning
confidence: 99%
“…They concluded from results that serum FGF23 level is independently associated with LVH; however, it is not a predictor for short-term prognosis (2-year follow-up). [22] In a recent study, Kovács and colleagues [23] by using three-dimensional speckle tracking echocardiography investigated the effects of FGF23 on LV mechanics in patients on hemodialysis and found that elevated FGF23 levels were associated with increased LV mass (ρ = 0.581, P < 0.001). Accordingly, Liu et al [24] examined the relationship between FGF23and LVH in 62 patients on continuous ambulatory peritoneal dialysis and 30 healthy controls [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Superiority of speckle tracking-derived parameters in detecting subtle myocardial injury was suggested by numerous works not just in humans but also in animal models (12,15,16). Strain indices were shown to be able to sensitively and continually reflect the progression of heart failure as well (13).…”
Section: H746 Speckle Tracking and P-v Analysis In Athlete's Heartmentioning
confidence: 96%
“…Most studies have used echocardiography to measure cardiac strain among patients with renal disease, and have reported an association between strain and cardiovascular outcomes. [16][17][18][19] In comparison to echocardiography, cardiac MRI (CMR) has the benefit of being less operator-dependent, more reproducible, and better equipped to study circumferential strain. 11 The increased availability and standardization of CMR have lent itself to strain analysis in research and clinical use.…”
Section: Introductionmentioning
confidence: 99%